Research on Three-Dimensional Magnetic Induced Error Model of Interferometric Fiber Optic Gyro - Zicheng Wang; Guochen Wang; Wei Gao; Zhuo Wang (IEEE Photonics Journal)
In practical, the Faraday effect-induced bias error is one of the main sources of bias error for the interferometric fiber optic gyroscope (IFOG). The Faraday effect-induced bias error impairs in the performance of IFOG. Normally, the Faraday effect-induced bias errors is hardly eliminated. To improve the performance of IFOG, the accurate model of Faraday effect-induced bias errors is necessary for its practical applications. In this paper, from the perspective of the finite element method, we calculate Faraday effect-induced bias errors of the fiber coil by the three-dimensional model in the radial magnetic field, and the axial magnetic field. Comparing with the traditional model, the differences mainly come from the size, and direction of the magnetic field, including the differences of the twist ratio, and the bending rate of each layer. Using the Jones matrix, we derive the three-dimensional magnetic field error model, further more theoretical results are obtained by simulation. The experiment with a 1024 m PM fiber coil are performed, and the experimental results support these theoretical predictions.